2022
DOI: 10.1590/s1980-657420220002022
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effect in Brazilian water polo: analysis of male and female athletes from U16 to senior categories

Abstract: To investigate the existence of relative age effect (RAE) in Brazilian water polo athletes according to sex and age category. Methods: The birthdate of 574 Brazilian water polo athletes were organized according to the athletes' birthdates into quarters of the year (Q1, Q2, Q3, and Q4), and classified according to sex (male and female) and age category (U16, U18, U20, and senior). To verify the existence of RAE, the Chi-Square tests (χ 2 ) were performed, and the effect sizes (ω) were calculated for each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Considering the multifactorial and context-specific nature of RAE, factors such as the athletes’ sex and competitive level within a sport may affect the likelihood of RAE occurrence (Castro et al, 2022b; Castro, Francisco, et al, 2022; Figueiredo et al, 2022; Smith et al, 2018; Wattie et al, 2015). Regarding sex differences, previous research found that RAE occurs to a smaller extent in women’s than in men’s sports (de la Rubia et al, 2020; Lidor et al, 2021; Parma & Penna, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the multifactorial and context-specific nature of RAE, factors such as the athletes’ sex and competitive level within a sport may affect the likelihood of RAE occurrence (Castro et al, 2022b; Castro, Francisco, et al, 2022; Figueiredo et al, 2022; Smith et al, 2018; Wattie et al, 2015). Regarding sex differences, previous research found that RAE occurs to a smaller extent in women’s than in men’s sports (de la Rubia et al, 2020; Lidor et al, 2021; Parma & Penna, 2018).…”
Section: Introductionmentioning
confidence: 99%